Is it possible to get COVID infection 3 times? Case report: Covid-19 reinfection - Chaves, Eunice Beatriz Martin; Dantas Filho, Fábio Fernandes; Schmidt Fernandes, Fernando; Muniz Fighera, Tayane; Pienis Callegaro, Fabiane (Clinical and Biomedical Research, 2023)
Rare cases of suspected COVID-19 reactivation have been reported. Reactivation is defined by two positive real-time RT-PCR results for the SARS-CoV-2 virus, with an interval equal to or greater than 90 days between two episodes of COVID-19. A nurse, started with COVID-19 symptoms in July 2020 and a RT-PCR SARS-CoV-2 confirmed the diagnosis. In November 2020, more than 4 months later, she developed a new episode of COVID-19 confirmed by a second RT-PCR SARS-CoV-2. The patient received a first dose of CoronaVac – (Sinovac/Butantan) in January 2021 and a second dose in February 2021, but 30 days after a third episode was confirmed. Contrary to what happens with many infectious diseases which generate antibodies and protect people from future episodes, this aspect is still not clear in relation to COVID-19. In addition to vaccination, the use of Personal Protective Equipment is essential for healthcare workers.